Comparative study on the bending of sandwich FGM beams made up of different material variation laws using refined layerwise theory. (December 2020) - Garg, Aman; Chalak, H.D.; Chakrabarti, Anupam
Abstract: Comparative study is carried out in present work on sandwich functionally graded beams made up of different material property variation laws. For study, power, exponential and sigmoidal laws are used. A fourth-order zigzag theory is used for the analysis. Both in-plane and transverse displacement fields are considered to predict the behavior of thick beams more efficiently. A 3-noded 1-D finite element having 8 degrees of freedom per node is used during analysis. The present model satisfies inter-laminar transverse stress continuity conditions at interfaces along with zero value at the top and bottom surfaces of the beam for transverse shear stresses. The current model is free from the requirement of any kind of penalty or C-1 conditions and hence is computationally efficient. Present results are validated with those available in the literature. Results for exponential and sigmoidal law are new results in present work, which will serve as a benchmark for future studies. Results for stresses and deflection are presented in form of tables. For some cases, stress variation across the thickness of beam are also reported. A modified form of exponential and sigmoidal law named Type-E1 and Type-S2 are also presented in which central core is made up of FGM phase. Among all the material variation laws, sandwich FGM beam having ceramic face sheets and exponentially varying FGM core (C-Type-E1) is found to perform best among all the cases studied. Highlights: Bending analysis of sandwich FGM beams using FE based HOZT. Formulation is free from any kind of penalty requirements. Modified form of exponential and sigmoidal laws are proposed. Comparative study between power, exponential and sigmoidal sandwich FGM beams.